Discovery and pharmacodynamic evaluation of the novel butene lactone derivative M355 against influenza A virus in vitro and in vivo. Issue 9 (20th May 2022) - Geng, Jingwei; Hu, Xiaoning; Zhang, Zhongmou; Gu, Zichen; Li, Yuanyuan; Mou, Xiaodong; Mao, Lu; Ge, Yongzhuang; Yang, Xinyu; Song, Yihui; Liu, Hongmin; Wang, Linqing; et al.
Abstract: A new series of butene lactone derivatives were designed according to an influenza neuraminidase target and their antiviral activities against H1N1 infection of Madin–Darby canine kidney cells were evaluated. Among them, a compound that was given the name M355 was identified as the most potent against H1N1 (EC50 = 14.7 μM) with low toxicity (CC50 = 538.13 μM). It also visibly reduced the virus‐induced cytopathic effect. Time‐of‐addition analysis indicated that H1N1 was mostly suppressed by M355 at the late stage of its infectious cycle. M355 inhibited neuraminidase in a dose‐dependent fashion to a similar extent as oseltamivir, which was also indicated by a computer modeling experiment. In a mouse model, lung lesions and virus load were reduced and the expression of nucleoprotein was moderated by M355 . The enzyme‐linked immunosorbent assay and quantitative real‐time polymerase chain reaction analyses revealed that the levels of interferon‐γ, interferon regulatory factor‐3, Toll‐like receptor‐3, tumor necrosis factor‐α, interleukin (IL)‐1β, IL‐6, and IL‐8 were downregulated in the M355 ‐treated groups, whereas the levels of IL‐10 and IL‐13 were upregulated. Similarly, IgG was found to be increased in infected mice plasma. These results demonstrate that M355 inhibit the expression of H1N1 in both cellular and animal models. Thus, M355 has the potential to be effective in the treatment of influenza A virus infection.